The Influence of Organizational Culture, Work Environment, Workload and Discipline on Teacher Performance - Erni Purwanti; Tri Ariprabowo; Sukaris Sukaris (INNOVATION RESEARCH JOURNAL, 2024)
ABSTRAK Penelitian ini dilakukan untuk menguji Pengaruh Budaya Organisasi, Lingkungan Kerja, Beban Kerja dan Disiplin Terhadap Kinerja Guru SMA Swasta X di Gresik. Untuk memenuhi hal tersebut dilakukan kajian literatur dan disposisi hipotesis, serta pengolahan data dari kuesioner yang dibagikan kepada 55 orang guru. Pemeriksaan dilakukan dengan menggunakan Total Sampling. Pengujiannya dengan menggunakan analisis regresi linier berganda. Hasil analisis menunjukkan bahwa Budaya Organisasi berpengaruh langsung terhadap kinerja guru, Lingkungan Kerja tidak berpengaruh terhadap kinerja guru, Beban Kerja berpengaruh langsung terhadap kinerja guru, Disiplin berpengaruh langsung terhadap kinerja guru. Kata Kunci: Budaya Organisasi, Lingkungan Kerja, Beban Kerja, Kedisiplinan, Kinerja Guru ABSTRACT This research was conducted to examine the influence of organizational culture, work environment, workload and discipline on the performance of teachers at Private High School X in Gresik. To fulfill this, a literature review and hypothesis disposition was carried out, as well as data processing from questionnaires distributed to 55 teachers. The examination was carried out using Total Sampling. The test uses multiple linear regression analysis. The results of the analysis show that Organizational Culture has a direct effect on teacher performance, Work Environment has no effect on teacher performance, Workload has a direct effect on teacher performance, Discipline has a direct effect on teacher performance. Key words: organizational culture, work environment, workload, discipline, teacher performance